Dairy ingredients for food processing - Chandan, Ramesh C.; Kilara, Arun.; Wiley InterScience (Online service) (Hoboken : Wiley-Blackwell, 2011)
"Unique in its perspective and scope, Dairy Ingredients for Food Processing gives a complete description of various dairy ingredients commonly used in food processing operations. Information is conveniently grouped under two sections. Section 1. Dairy Ingredients: Basic Technology includes chapters covering an overview of the milk composition, physical, chemical and functional properties, and basic dairy processing principles to describe how various ingredients are engineered for functional quality related to food processing. Additional chapters highlight production and specifications of various condensed milk products, dry milk products, and whey products. Other chapters address milk fat concentrates (cream, butter, and anhydrous butterfat), processing and specifications of cheese and cheese products, enzyme modified cheese, cheese sauce and dry cheese products, and fermented dairy ingredients. Information is provided on microbiological considerations relative to dairy processing, nutrition and health, frozen dairy ingredients, and dairy desserts as well as labeling and regulatory compliance. Coverage in Section 2. Dairy Ingredients: Applications describes the applied aspects of using dairy ingredients in food products such as bakery products, chocolates and confectionery, snack foods, meats, sauces, dressings, desserts, infant formulas, puddings, and functional foods. Shelf life and safety issues are also addressed. All technology and applications chapters are supported by sound scientific and engineering principles. The book presents a contemporary update and a unique approach to the topics, and is designed to augment related books in the existing market. The editorial team is comprised of individuals with significant experience in the science and applications of dairy products manufacture as well their industrial use in various food products. Intended for professionals in the dairy and food industry, Dairy Ingredients for Food Processing also appeals to professors and students in food science for its contemporary information and experience-based applications"--
"Unique in its perspective and scope, Dairy Ingredients for food processing gives a complete description of various dairy ingredients commonly used in food processing operations. Section 1 of the text includes chapters on milk composition, functional properties, and basic dairy processing principles. Section 2 describes the applied aspects of using dairy ingredients in food products such as bakery products, confectionery, snack foods, dressings, desserts, infant formulas, puddings, and functional foods. The book presents a contemporary approach to the topics, and is designed to augment related books in the existing market"--
Front Matter -- Dairy Ingredients for Food Processing: An Overview / Ramesh C Chandan -- Chemical, Physical, and Functional Characteristics of Dairy Ingredients / Stephanie R Pritchard, Kasipathy Kailasapathy -- Microbiological Aspects of Dairy Ingredients / Michael Rowe, John Donaghy -- Processing Principles of Dairy Ingredients / Arun Kilara -- Concentrated Fluid Milk Ingredients / Nana Y Farkye, Shakeel ur-Rehman -- Dry Milk Ingredients / Mary Ann Augustin, Phillip Terence Clarke -- Casein, Caseinates, and Milk Protein Concentrates / Mary Ann Augustin, Christine M Oliver, Yacine Hemar -- Whey-Based Ingredients / Lee M Huffman, Lilian de Barros Ferreira -- Butter and Butter Products / Anna M Fearon -- Principles of Cheese Technology / Ramesh C Chandan, Rohit Kapoor -- Manufacturing Outlines and Applications of Selected Cheese Varieties / Ramesh C Chandan, Rohit Kapoor -- Enzyme-modified Dairy Ingredients / Arun Kilara, Ramesh C Chandan -- Fermented Dairy Ingredients / Junus Salampessy, Kasipathy Kailasapathy -- Functional Ingredients from Dairy Fermentations / Ebenezer R Vedamuthu -- Dairy-based Ingredients: Regulatory Aspects / Dilip A Patel -- Nutritive and Health Attributes of Dairy Ingredients / Ramesh C Chandan -- Dairy Ingredients in Dairy Food Processing / Tonya C Schoenfuss, Ramesh C Chandan -- Dairy Ingredients in Bakery, Snacks, Sauces, Dressings, Processed Meats, and Functional Foods / Ramesh C Chandan -- Dairy Ingredients in Chocolate and Confectionery Products / Jorge Bouzas, Steven Hess -- Dairy Ingredients in Infant and Adult Nutrition Products / Jeffrey Baxter, Steven Dimler, Nagendra Rangavajala -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Dairy processing; Dairy products; Dairy microbiology; Llet -- Tractament; Productes lactis; TECHNOLOGY & ENGINEERING -- Food Science; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Dairy microbiology; Dairy processing; Dairy products; Electronic books